EFEKTIVITAS MODEL PROJECT BASED LEARNING TERHADAP HASIL BELAJAR IPAS SISWA KELAS V SEKOLAH DASAR - Listya Ababil; Anggit Grahito Wicaksono; Oka Irmade (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to analyze the effectiveness of the Project Based Learning (PjBL) model in improving fifth-grade elementary school students' learning outcomes in Science and Social Studies (IPAS). The study employed a quantitative approach using a quasi-experimental method with a Nonequivalent Control Group Design. The sample consisted of 54 students, including 28 students in the experimental class and 26 students in the control class. Data were collected using a learning achievement test that had met the requirements of validity, reliability, item difficulty, and discrimination index. Data analysis included the Kolmogorov–Smirnov normality test, Levene's Test for homogeneity, Normalized Gain (N-Gain) analysis, and the Independent Sample t-Test using IBM SPSS Statistics. The findings revealed that the experimental class achieved an average N-Gain of 64.10%, categorized as moderately effective, while the control class obtained 33.81%, categorized as less effective. The Independent Sample t-Test indicated a significance value of 0.000 (<0.05), demonstrating a significant difference in learning improvement between the two groups. Therefore, the Project Based Learning model was more effective than conventional learning in improving elementary school students' IPAS learning outcomes.